Multiple directorships, family ownership and the board nomination committee: International evidence from the GCC - Eulaiwi, B.; Al-Hadi, A.; Taylor, G.; Al-Yahyaee, K.; Evans, John (Elsevier BV, 2015)
In this paper, we investigate the association between outside board directorships and family ownership concentration. Using a sample of 1091 firm-year observations of non-financial publicly listed firms from Gulf Cooperation Countries (GCC) during the 2005 to 2013 period, we find a positive association between family ownership and the number of outside directorships held by board members. This finding is consistent with the notion that family ownership reduces a board's monitoring capabilities. We also test whether the recent corporate governance reforms in GCC, which were designed to protect investors and minority shareholders, affect firms' incentives to establish a board nomination committee (NC). We find the existence of a board NC and the quality and characteristics of NC membership act to suppress the positive association between outside directorships and family ownership. Our results are robust to the use of alternative measures of outside directorships and family ownership and models that test for endogeneity. Overall, our results suggest that the institutional specificities of emerging economies such as those in the GCC can sustain high levels of multiple directorships, which could impair the quality of corporate governance.